Study of the Effect of Nanostructured Grains on the Radiation Resistance of Zirconium Dioxide Ceramics During Gas Swelling in the Case of High-Dose Irradiation with He2+ Ions - Kozlovskiy, Artem L.; Konuhova, Marina; Shlimas, Dmitriy I.; Borgekov, Daryn B.; Zdorovets, Maxim V.; Shakirziyanov, Rafael I.; Garanin, Yuriy A.; Volodina, Natalia O.; Popov, Anatoli I. (Engineered Science Publisher, 2024)
The paper is devoted to the study of the influence of variation of ZrO2 ceramics grain sizes on the resistance to radiation-induced swelling under irradiation with low-energy Не2+ ions. The choice of ZrO2 ceramics as objects of research is due to high levels of mechanical strength and hardness, as well as low rates of thermal expansion, which eliminates the effects of thermal expansion and destruction when operating at high temperatures, as well as good insulating properties, which makes it possible to use these ceramics both as radiation-resistant materials in nuclear energy in the manufacture of inert matrices of dispersed nuclear fuel, and as a basis for creation of fuel cells for the production of hydrogen. During the studies of the influence of mechanochemical grinding conditions on the change in dimensional factors in ZrO2 ceramics, it was found that increasing the grinding speed from 300 to 900 rpm does not lead to the initiation of polymorphic transformation processes of the m-ZrO2 → t-ZrO2 type, which are also not initiated during thermal annealing of samples at a temperature of 1500 °C, the choice of which was due to thermal relaxation of structural deformation distortions caused by mechanochemical grinding during grain crushing. In determining the influence of size effects (dislocation strengthening) on the resistance of ZrO2 ceramics to radiation-induced swelling under high-dose irradiation with He2+ ions, it was found that a decrease in grain size by 2.5 – 3 times leads to an increase in resistance to swelling and softening by 1.5 – 2 times. Moreover, for ZrO2 ceramic samples obtained at grinding speeds of 700 – 900 rpm, strengthening is not only due to dimensional factors, but also to the structural ordering of the crystal lattice, due to thermal relaxation of residual mechanical stresses. © Engineered Science Publisher LLC 2024. --//-- This is an open-access article Kozlovskiy, Artem L. and Konuhova, Marina and Shlimas, Dmitriy I. and Borgekov, Daryn B. and Zdorovets, Maxim V. and Shakirziyanov, Rafael I. and Garanin, Yuriy A. and Volodina, Natalia O. and Popov, Anatoli I., "Study of the Effect of Nanostructured Grains on the Radiation Resistance of Zirconium Dioxide Ceramics During Gas Swelling under High-dose Irradiation with Helium Ions", ES Materials & Manufacturing, 2024, volume 24, DOI 10.30919/esmm1165.
This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (No. BR18574135). In addition, M. K and A.I.P. were supported by EUROfusion Enabling Research Project ENR-MAT.02.ISSP-UL- \u201CNew dielectric functional materials and interfaces (DFMI) \u2013 Theoretical and Experimental analysis.\u201D This work has been carried out within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No 101052200 \u2014 EUROfusion). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. The research was performed in the Center of Excellence of the Institute of Solid-State Physics, University of Latvia, supported through European Unions Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Ceramics; Dislocation strengthening; Gas swelling; Radiation damage; Size effect; Zirconium dioxide